A Two-Stage Optimisation Method for Full-Scale Marine Propellers Working Behind a Ship. Issue 2 (May 2014) - Berger, Stephan; Druckenbrod, Markus; Pergande, Markus; Abdel-Maksoud, Moustafa
Abstract : A procedure for the optimisation of full-scale marine propellers working behind a ship is presented. The procedure consists of two stages, the actual optimisation and a detailed investigation of selected propeller variants. In the first stage, an evolutionary algorithm in combination with the in-house panel code panMARE is used to solve the multi-objective propeller optimisation problem. Efficient methods for the evaluation of propeller variants and parameterisation of propeller shape are presented. Proceeding from the results of the optimisation, a set of selected propeller variants is investigated in the second stage taking into account all relevant propeller-hull interactions. The applied algorithm is based on coupling of panMARE with a viscous flow solver. An enhancement of this method allows investigating several propeller variants sequentially without stopping the solvers. In this work, the optimisation method is applied to improve the propeller of a container vessel.